The novelties in the legislation of the Russian Federation on public financial control - Yalbulganov, Alexander (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2014)
The article studies the new legislation of the Russian Federation on public financial control. The author justifies the idea of reforming financial control through the need to fight corruption, which has obtained a warning scale in Russia and threatens the state’s foundations. The article contains an analysis of the powers vested in external and internal state financial control institutions, of entities subject to control and methods of control. The author notes that representations and ordinances issued by control and accounting institutions, based on the results of control activities, are designed to force the violators of financial discipline to eliminate the revealed violations. The author concludes that the necessary condition for effective implementation of public financial control is its clear legal regulation. The article stresses that the improvement in financial control in Russia is based on clearly stated principles, in accordance with international legal principles of independent auditing (control).